(untitled) (ARQUISUR Revista, 2018)
The following article analyzes a particular case of educational architecture, which demonstrates in itself the variations that have occurred throughout national history in the field of educational policy oriented to technical schools. The study of Paraná School No. 100 with guidance in Tecnico / a Naval allows us to visualize the complex relationship that is established between three variables such as: public educational policies, pedagogical proposals and the architectural support that is offered to them. A relationship full of disagreements, contradictions and misunderstandings that during different times put their emphasis on one of these three parts without the others respond equally.